Análisis multitemporal de las coberturas de la tierra en el municipio de Paz de Río, Boyacá durante el periodo 1986-2023 (2023)
In this study, a multi-temporal analysis of land cover change was conducted in the municipality of Paz de Río, Boyacá, spanning the period from 1986 to 2023, using geographic information system (GIS) tools. Satellite images captured by the Landsat sensor in the years 1986, 2000, 2016, and 2023 were employed. These images underwent digital processing in Erdas Imagine software to enhance their quality and resolution, thereby facilitating supervised classification in ArcGIS Pro software using the Maximum Likelihood algorithm.